Digitalisasi Bisnis Coffeshop: Tantangan Dan Dorongan Pada Inclusive Business Environment - Khusnul Khotimah; Nurul Asfiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the digital era that continues to develop, digitalization is a crucial aspect for business transformation in various sectors, including the coffee shop industry. This study investigates the influence of digitalization on the coffeeshop business by taking a case study at AADK Malang. This research identifies the challenges and incentives faced by AADK in adopting digital technology, as well as its impact on an inclusive business environment. Through bibliometric analysis and case studies, it was found that digitalization provides significant benefits in the form of increased operational efficiency and expanded customer reach, but also raises challenges such as initial investment costs, data security and system integration. The results of this research are that the challenges faced in implementing digitalization include significant initial investment costs, system integration difficulties, employee training, data security, and changes in organizational culture. However, the drive to adopt inclusive business models through digitalization is also strong, including increased accessibility, better customer engagement, operational process optimization and market expansion